PELAYANAN KESEHATAN PRIMER SEBAGAI GATEKEEPER DAN KEBIJAKAN DISKUSI PEER REVIEW: ANTARA KUALITAS DAN REALITAS UNTUK MENURUNKAN KASUS RUJUKAN NON SPESIALISTIK - Zahrina, Zahrina; Ramadani, Royasia Viki; Hulwah, Khairun Nisa il; Nurlatifah, Siti; Andalan, Aldi; Gani, Ascobat; Kurniawaty, Golda; Setiawan, Ery (Jurnal Ekonomi Kesehatan Indonesia, 2023)
Almost 80% of the source of funds is spent on hospital. This situation indicates the failure of the gatekeeper function in primary health care. Performance-based capitation is implemented to ensure the cost and quality of primary care, with non-specialist referral rate as one of the particular parameters. The peer review policy is a discussion between BPJS Health, District/City Health Services, IDI, provincial and branch Team of KMKB and other relevant stakeholders to determine which diagnoses must be handled at FKTP also to accommodate and improve the capacity of FKTP to handle patients and minimize referral cases. This study aims to evaluate the implementation of peer review discussions and analyze the obstacles, challenges and potential of peer review policies to optimize the FKTP gatekeeper function. The research method is qualitative, and it involves conducting in-depth interviews, FGDs, and literature reviews. In general, the peer review policy is quite good in controlling referral cases, especially RNS (Non-Specialist Referrals). In general, the peer review policy is entirely reasonable to control referral cases, especially RNS. Evaluation of the "peer review discussion" policy on the communication aspect is the lack of socialization regarding the management of tiered referrals. Resources, especially human resources, health equipment and drugs, still need to be increased in FKTP. Payment mechanisms such as capitation are essential to adjust the risk and capacity of FKTP or incentive mechanisms—determination of PPK on FKTP, clear boundaries and medical authority for FKTP and FKRTL. As well as, the role and coordination among stakeholders need to be improved to strengthen the prerequisites for FKTP infrastructure.